The landscape archaeology of Anglo-Saxon England - Higham, N. J.; Ryan, Martin J. (Pubns Manchester Centre for Anglo-Saxon Studies, 9., 2010)
"Traditional opinion has perceived the Anglo-Saxons as creating an entirely new landscape from scratch in the fifth and sixth centuries AD, cutting down woodland, and bringing with them the practice of open field agriculture, and establishing villages. Whilst recent scholarship has proved this simplistic picture wanting, it has also raised many questions about the nature of landscape development at the time, the changing nature of systems of land management, and strategies for settlement. The papers here seek to shed new light on these complex issues. Taking a variety of different approaches, and with topics ranging from the impact of coppicing to medieval field systems, from the representation of the landscape in manuscripts to cereal production and the type of bread the population preferred, they offer striking new approaches to the central issues of landscape change across the seven centuries of Anglo-Saxon England, a period surely foundational to the rural landscape of today.BR> Nicholas J. Higham is Professor of Early Medieval and Landscape History at the University of Manchester; Martin J. Ryan lectures in Medieval History at the University of Manchester. Contributors: Nicholas J. Higham, Christopher Grocock, Stephen Rippon, Stuart Brookes, Carenza Lewis, Susan Oosthuizen, Tom Williamson, Catherine Karkov, David Hill, Debby Banham, Richard Hoggett, Peter Murphy."